Editors' Choice—A Monolithic Photoelectrochemical Device Evolving Hydrogen in Pure Water. Issue 13 (6th September 2019) - Kistler, Tobias A.; Danilovic, Nemanja; Agbo, Peter
Abstract : We report the development of a fully-integrated, photoelectrochemical (PEC) device coupling water oxidation to hydrogen evolution using a III-V triple-junction photovoltaic (PV) embedded in a Nafion membrane. This architecture is genuinely monolithic, with wireless catalyst integration being achieved via compression of metal sputter-coated carbon electrodes against the front and back PV contacts. The resulting MEA-type, sandwich structure minimizes the path length for proton conduction through the membrane ionomer, while simultaneously preventing PV light attenuation by the catalyst layer, a common issue for monolithic PEC structures. Simulated, solar illumination of this construct, when operating in neutral-pH water, yields a peak solar-to-hydrogen efficiency of 12.6% during a four-day trial. While the wireless nature of monolithic PEC devices typically prevents the measurement of current flow and faradaic efficiencies, we circumvent this complication through the placement of an electrical shunt between the PV and the cathode catalyst layer, rerouting charge generated at the PV through a potentiostat prior to cathodic proton reduction. Using this configuration, we also show evidence of a corrosion current competing with anodic oxygen evolution under acidic conditions, highlighting the importance of quantifying product generation in monolithic devices.